Straw core-based composite film as well as preparation method and application thereof

By using a composite film prepared by straw core particles, polyethylene glycol, and bone gel, and coating polyethylene glycolinyl alcohol on its surface, the problem of poor environmental protection and cost of food packaging materials has been solved. Green food packaging materials that block performance.

CN119371703APending Publication Date: 2025-01-28HEBEI YEZHIYUAN CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411476107.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The poor environmental protection and high production cost of existing food packaging materials, especially the use of expensive nanofibers, limits their large-scale applications.

Method used

The straw core particles are used as the basic material, combined with cheap polyvinyl alcohol and bone glue as a binder, and coating polyethylene glycol alcohol -ditchyhyde on the surface of the membrane substrate to form a water -sparse layer to prepare a green and environmentally friendly composite film.

Benefits of technology

This composite film not only has good mechanical strength and toughness, but also has excellent water vapor blocking performance. It is suitable for food packaging and is low in cost and conforms to the development concept of green chemistry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371703A_ABST
    Figure CN119371703A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of materials, and particularly discloses a straw core-based composite film as well as a preparation method and application thereof. The straw core-based composite membrane comprises a membrane base material composed of straw core particles and a hydrophobic layer coating the surface of the membrane base material, polyvinyl alcohol and bone glue are filled among the straw core particles; the hydrophobic layer is made of polyvinyl butyral. The polyvinyl alcohol has good film-forming property and certain plasticity and can form a framework sufficient for supporting the straw core particles to be formed, the periosteum formed by the bone glue has the characteristics of firmness and high resilience, and the interlayer of the straw core particles is filled with the bone glue, so that the water vapor barrier property of the composite film can be further improved; the polyvinyl alcohol and the bone glue cooperate to promote the forming of the straw core particles, so that the film base material has high strength and water vapor barrier property, and the surface of the film base material is coated with the polyvinyl butyral, so that the mechanical strength, the water vapor barrier property and the stability in practical application of the composite film are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material technology, and in particular to a straw core-based composite film and a preparation method and application thereof. Background Art

[0002] With the rapid development of the modern economy, the food delivery and logistics industries have gradually become part of people's lives, and the demand and requirements for commodity and food packaging materials are also increasing. Traditional petroleum-based plastics remain the main source of packaging materials and are widely used in daily life due to their durability and convenience. However, their non-degradability limits their long-term development. Currently, there are reports on using corn straw cobs (CSC) as a base material and using polyethylene oxide (PEO), nanofibers (CNFs), and polyphenol functional compounds to improve the toughness and strength of composite films. Although the prepared composite films have good strength, toughness, antioxidant and antibacterial properties, the high cost of CNFs limits their large-scale application. Therefore, how to design a new material that is green, environmentally friendly, low-cost, and particularly suitable for food packaging is an urgent problem to be solved by those skilled in the art. Summary of the Invention

[0003] To address the problems of poor environmental friendliness and high production costs of existing food packaging materials, the present invention provides a straw-core-based composite film, its preparation method, and its application. The present invention uses straw core microparticles as the base material, and uses inexpensive polyvinyl alcohol and bone glue as binders to fill the space between the straw core microparticles to form a membrane substrate. Polyvinyl butyral is then dip-coated on the surface of the membrane substrate to form a hydrophobic layer. The resulting composite film not only has relatively good mechanical strength and toughness, but also has excellent water vapor barrier properties, and has broad application prospects in the field of preparing water-blocking and breathable materials.

[0004] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0005] In a first aspect, the present invention provides a straw core-based composite membrane, comprising a membrane substrate composed of straw core particles and a hydrophobic layer coated on the surface of the membrane substrate;

[0006] Wherein, polyvinyl alcohol and bone glue are filled between the straw core particles;

[0007] The material of the hydrophobic layer includes polyvinyl butyral.

[0008] Compared with the prior art, the straw core-based composite film provided by the present invention uses straw core particles as the base material, and polyvinyl alcohol and bone glue as fillers and binders, wherein polyvinyl alcohol (PVA) has good film-forming properties and a certain plasticity, and can form a skeleton sufficient to support the molding of straw core particles. The periosteum formed by bone glue (BG) has the characteristics of being strong and elastic. Filling the interlayer of straw core particles with bone glue can further improve the water vapor barrier property of the composite film; polyvinyl alcohol and bone glue synergistically promote the molding of straw core particles, so that the film substrate has higher strength and water vapor barrier property, solving the problem that straw core particles cannot form a film and the mechanical strength is low after film formation using other binders; coating polyvinyl butyral on the surface of the film substrate further improves the mechanical strength, water vapor barrier property and stability of the composite film in practical applications.

[0009] The straw core-based composite film provided by the present invention uses raw materials such as straw core, polyvinyl alcohol, skeleton and polyvinyl butyral, which are all green, environmentally friendly, biodegradable and inexpensive, conform to the development concept of green chemistry, and have sufficient stability in actual use, and have extremely high promotion and application value.

[0010] Furthermore, the particle size of the straw core particles is 200-400 meshes.

[0011] Specifically, the straw core particles include one or more of corn straw core particles, sunflower straw core particles or sesame straw core particles.

[0012] Furthermore, the alcoholysis degree of the polyvinyl alcohol is 87% to 89%.

[0013] Furthermore, the average molecular weight of the polyvinyl butyral is 90,000 to 120,000.

[0014] Polyvinyl alcohol provides the necessary plasticity for the straw-core microparticle film, and as a binder and filler, it enhances the toughness of the film's base skeleton. The presence of gelatin provides sufficient hardness for the composite film, while the surface-coated polyvinyl butyral ensures sufficient stability in humid environments. Furthermore, the gelatin and polyvinyl butyral filler between the layers of the straw-core microparticles significantly improves the composite film's barrier properties.

[0015] Furthermore, the thickness of the film substrate is 150 μm to 180 μm.

[0016] Furthermore, the penetration thickness of the hydrophobic layer in the membrane substrate is 5 μm to 20 μm.

[0017] Furthermore, the mass ratio of the straw core particles, polyvinyl alcohol, bone glue and polyvinyl butyral is 2:(0.5-1):(0.5-1):(0.5-2).

[0018] In a second aspect, the present invention further provides a method for preparing a straw core-based composite film, the preparation method comprising at least the following steps:

[0019] S1, dissolving polyvinyl alcohol and bone glue in water to obtain polyvinyl alcohol solution and bone glue solution respectively;

[0020] dissolving polyvinyl butyral in an alcohol solvent to obtain a polyvinyl butyral solution;

[0021] S2, uniformly mixing the straw core particles, polyvinyl alcohol solution and gelatin solution, and casting the mixture into a film to obtain a film substrate;

[0022] S3, adding the membrane substrate into a polyvinyl butyral solution, impregnating, and drying to obtain a straw core-based composite membrane.

[0023] The preparation method of the straw core-based composite film provided by the present invention comprises the following steps: straw core particles, polyvinyl alcohol and bone glue are first formed by tape casting, the straw core particles are first deposited and stacked during the tape casting process, and as the solvent is removed, polyvinyl alcohol and bone glue slowly gather between and on the surface of the straw core particles to obtain a film substrate. Due to the large size of the straw core particles, they are first settled by gravity to form a reverse (bottom) lamella structure. During the drying process, as the water slowly evaporates, the polyvinyl alcohol dissolved therein is synchronously dispersed between the lamellae of the straw core particles, forming an adhesive effect. The polyvinyl alcohol segments with larger molecular weight are blocked by the lamella structure and gather on the substrate surface to form a front compact structure. The front (top) of this film substrate exhibits a smooth and hydrophobic characteristic, while the reverse (bottom) of the film substrate presents a lamella loose structure, which exhibits a hydrophilic characteristic. This structure enables the front of the composite film to remain stable in a humid environment, while the reverse of the composite film remains stable in a dry environment, providing a new idea for the application of the composite film in an environment with a humidity difference on both sides. Then, the membrane substrate is immersed in a polyvinyl butyral solution, so that the polyvinyl butyral is coated on the surface of the straw core particles and even penetrates into the gaps between the straw core particles, ensuring the stability of the composite membrane in water or a humid environment and having a certain toughness.

[0024] As a specific embodiment of the present invention, the preparation method of the straw core microparticles is: taking straw cores, drying them at 50° C. to 60° C. for more than 24 hours, crushing and sieving to obtain straw core microparticles.

[0025] Furthermore, the concentration of the polyvinyl alcohol solution is 5wt% to 10wt%.

[0026] As a specific embodiment of the present invention, the preparation method of the polyvinyl alcohol solution is: add polyvinyl alcohol to deionized water, heat it to 70℃~90℃, stir it at 500r / min~700r / min for 1h, cool it to room temperature and continue stirring until the solution is transparent to obtain the polyvinyl alcohol solution.

[0027] Furthermore, the concentration of the bone glue solution is 5wt% to 10wt%.

[0028] As a specific embodiment of the present invention, the preparation method of the bone glue solution is: adding bone glue into deionized water, stirring at 500r / min to 700r / min at room temperature until completely dissolved, to obtain the bone glue solution.

[0029] Furthermore, the concentration of the polyvinyl butyral solution is 5wt% to 15wt%.

[0030] As a specific embodiment of the present invention, the preparation method of the polyvinyl butyral solution is: adding polyvinyl butyral to an alcohol solvent, stirring at 500 r / min to 700 r / min until completely dissolved, to obtain the polyvinyl butyral solution.

[0031] Specifically, the alcohol solvent is anhydrous ethanol.

[0032] By controlling the concentrations of the polyvinyl alcohol solution, the gelatin solution and the polyvinyl butyral solution, the dispersion of the straw core particles in the solution and the coating of the hydrophobic layer are facilitated.

[0033] Furthermore, in S2, the straw core particles, the polyvinyl alcohol solution and the gelatin solution are stirred at 500 r / min to 700 r / min for 10 h to 14 h to uniformly mix.

[0034] Exemplarily, in S2, the mixed solution is poured into a PTFE mold and dried by air blowing to obtain a membrane substrate.

[0035] Specifically, the air drying temperature is 50° C. to 70° C., and the drying time is 5 hours to 7 hours.

[0036] Furthermore, in S3, the immersion temperature is 20°C to 40°C, and the immersion time is 12h to 48h.

[0037] By controlling the immersion time of the film substrate in the polyvinyl butyral solution, it can be ensured that the polyvinyl butyral molecular chains are fully attached to the surface of the substrate.

[0038] For example, in S3, the drying temperature is 50° C. to 70° C., and the drying time is 10 min to 20 min.

[0039] The preparation method of the straw core-based composite film provided by the present invention adopts the methods of co-mixing, tape casting and soaking to prepare the composite film. The method is simple and suitable for industrial-scale production.

[0040] In a third aspect, the present invention further provides the use of the straw core-based composite membrane in the preparation of a water-blocking and breathable membrane.

[0041] Furthermore, the water-blocking and breathable film is a packaging film, a moisturizing film, a sealing film or an inner core layer of a mask.

[0042] Compared with the prior art, the straw core-based composite film provided by the present invention has good strength and toughness, and the water vapor permeability coefficient is 1.05658*10 -13 g*cm*cm -2 *s -1 *Pa -1 , the natural degradation time is about 3 months; at the same time, the preparation method of the composite membrane of the present invention is simple, the structural stability of the prepared composite membrane is high, it is easy to realize industrial application, and the application prospect is broad. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The SEM images of the composite membranes prepared in Comparative Example 6 and Example 2, wherein: a: front SEM image of the composite membrane of Comparative Example 6; b: back SEM image of the composite membrane of Comparative Example 6; c: cross-sectional SEM image of the composite membrane of Comparative Example 6; d: SEM image of the surface of the composite film prepared in Example 2;

[0044] Figure 2 The SEM images of the cross sections of the straw core-based composite membranes prepared in Examples 1 to 4 are as follows;

[0045] Figure 3 FT-IR infrared spectra of corn straw cob (CSC), polyvinyl alcohol (PVA), bone glue (BG), polyvinyl butyral (PVB), samples prepared in Examples 1 to 4, and Comparative Example 6;

[0046] Figure 4 The water contact angle data of the samples prepared in Examples 1 to 4 and Comparative Example 6 are shown;

[0047] Figure 5 Comparison of water vapor permeability coefficients of samples prepared in Examples 1 to 4 and Comparative Example 6 with those of polylactic acid (PLA), polybutylene terephthalate-adipate (PBAT), CNF / CSC-100 (CN115926486A), and CCP-VVE-2 (CN117050386A);

[0048] Figure 6 A comparison chart of water absorption and dissolution rates of samples prepared in Examples 1 to 4 and Comparative Example 6;

[0049] Figure 7 This is a comparison chart of the tensile strength and elongation at break of the samples prepared in Examples 1 to 4 and Comparative Example 6. DETAILED DESCRIPTION

[0050] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the examples. It should be understood that the specific embodiments described herein are merely for the purpose of explaining the present invention and are not intended to limit the present invention. Unless otherwise specified, the raw materials used in the following examples and comparative examples are all commercially available materials.

[0051] The sources of raw materials used in the following examples and comparative examples are as follows:

[0052] Corn straw cobs (CSC) were sourced from Daxin Village, Xiajiaying Town, Jiaocheng County, Lüliang City, Shanxi Province.

[0053] Polyvinyl alcohol (PVA) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., CAS No. 9002-89-5; bone glue (BG) was an industrial-grade product; polyvinyl butyral (PVB) was purchased from Shandong Keyuan Biochemical Co., Ltd., CAS No. 63148-65-2, MW: 90,000-120,000; carrageenan was an industrial-grade product.

[0054] The preparation method of corn straw core microparticles is as follows: taking corn straw cores, drying them at 60° C. for 24 hours, crushing them, and passing them through a 200-mesh sieve to obtain corn straw core microparticles.

[0055] The preparation method of the polyvinyl alcohol aqueous solution is as follows: add polyvinyl alcohol to deionized water, heat to 80° C., stir at 600 r / min for 1 hour, cool to room temperature, and continue stirring until transparent to obtain a polyvinyl alcohol aqueous solution with a concentration of 7.5 wt %.

[0056] The preparation method of the bone glue aqueous solution is as follows: adding bone glue into deionized water, stirring at 600 r / min at room temperature until the solution is completely dissolved, and obtaining a bone glue aqueous solution with a concentration of 10 wt%.

[0057] The preparation method of the carrageenan aqueous solution is as follows: adding carrageenan into deionized water, stirring at 600 r / min at room temperature until the carrageenan is completely dissolved, and obtaining a carrageenan aqueous solution with a concentration of 10 wt %.

[0058] The preparation method of the polyvinyl butyral solution is as follows: polyvinyl butyral is added into anhydrous ethanol, and stirred at 600 r / min at room temperature until the solution is completely dissolved, thereby obtaining a polyvinyl butyral solution with a concentration of 5 wt %.

[0059] Example 1

[0060] The embodiment of the present invention provides a method for preparing a straw core-based composite film, the preparation method comprising the following steps:

[0061] Step 1: Weigh 150 mg of corn straw core microparticles into a beaker, weigh 1 g of a 7.5 wt% polyvinyl alcohol aqueous solution and pour it into the beaker, then weigh 0.75 g of a 10 wt% bone glue aqueous solution, add deionized water and dilute to 4 g, stir at room temperature for 2 h at a speed of 600 r / min, pour into a PTFE mold, and place in a 60°C forced air drying oven until a film is formed to obtain a membrane substrate;

[0062] Step 2: soak the above membrane substrate in a 5 wt % polyvinyl butyral solution at room temperature for 12 h, take it out, place it in a 60° C. forced air drying oven, and dry it for 15 min to obtain a straw core-based composite membrane, which is designated as CPBP-12h.

[0063] Example 2

[0064] The embodiment of the present invention provides a method for preparing a straw core-based composite film, the preparation method comprising the following steps:

[0065] Step 1: Weigh 150 mg of corn straw core microparticles into a beaker, weigh 0.5 g of a 7.5 wt% polyvinyl alcohol aqueous solution and pour it into the beaker, then weigh 0.75 g of a 10 wt% bone glue aqueous solution, add deionized water and dilute to 4 g, stir at room temperature for 2 h at a speed of 600 r / min, pour into a PTFE mold, and place in a 60°C forced air drying oven until a film is formed to obtain a membrane substrate;

[0066] Step 2: soak the above membrane substrate in a 5 wt % polyvinyl butyral solution at room temperature for 12 h, take it out, place it in a 60° C. forced air drying oven, and dry it for 15 min to obtain a straw core-based composite membrane, which is designated as CPBP-24h.

[0067] Example 3

[0068] The embodiment of the present invention provides a method for preparing a straw core-based composite film, the preparation method comprising the following steps:

[0069] Step 1: Weigh 150 mg of corn straw core microparticles into a beaker, weigh 1 g of a 7.5 wt% polyvinyl alcohol aqueous solution and pour it into the beaker, then weigh 0.38 g of a 10 wt% bone glue aqueous solution, add deionized water and dilute to 4 g, stir at room temperature for 2 h at a speed of 600 r / min, pour into a PTFE mold, and place in a 60°C forced air drying oven until a film is formed to obtain a membrane substrate;

[0070] Step 2: soak the above membrane substrate in a 5 wt % polyvinyl butyral solution at room temperature for 36 h, then take it out and place it in a 60° C. forced air drying oven for 15 min to obtain a straw core-based composite membrane, which is designated as CPBP-36h.

[0071] Example 4

[0072] The embodiment of the present invention provides a method for preparing a straw core-based composite film, the preparation method comprising the following steps:

[0073] Step 1: Weigh 150 mg of corn straw core microparticles into a beaker, weigh 1 g of a 7.5 wt% polyvinyl alcohol aqueous solution and pour it into the beaker, then weigh 1.5 g of a 10 wt% bone glue aqueous solution, add deionized water and dilute to 4 g, stir at room temperature for 2 h at a speed of 600 r / min, pour into a PTFE mold, and place in a 60°C forced air drying oven until a film is formed to obtain a membrane substrate;

[0074] Step 2: soak the above membrane substrate in a 5 wt % polyvinyl butyral solution at room temperature for 36 h, then take it out and place it in a 60° C. forced air drying oven for 15 min to obtain a straw core-based composite membrane, which is designated as CPBP-48h.

[0075] In the above embodiments 1 to 4, polyvinyl alcohol solutions, gelatin solutions, and polyvinyl butyral solutions of other concentrations defined in the present invention may also be used. As long as they are within the scope defined in the present invention, they can achieve technical effects equivalent to those of the corresponding embodiments.

[0076] Comparative Example 1

[0077] Weigh 150 mg of corn straw core particles into a beaker, add 3 g of deionized water, stir at room temperature for 2 h, rotate at 600 r / min, pour into a PTFE mold, and place in a 60°C forced air drying oven. After drying, the sample is obtained and recorded as CSC. The sample is not formed and does not need to be tested.

[0078] Comparative Example 2

[0079] Weigh 1 g of a 7.5 wt% polyvinyl alcohol aqueous solution and pour it into a beaker. Continue to weigh 0.75 g of a 10 wt% bone glue aqueous solution, add deionized water and dilute to 4 g. Stir at room temperature for 2 h at a speed of 600 r / min, pour into a PTFE mold, and place in a 60°C forced air drying oven until a film is formed. The sample is recorded as PVA / BG. The sample is completely brittle and does not need to be tested.

[0080] Comparative Example 3

[0081] The only difference between this comparative example and Example 1 is that no bone glue and polyvinyl butyral are added. The specific steps are as follows:

[0082] Weigh 150 mg of corn straw core microparticles and put them into a beaker. Weigh 1 g of 7.5 wt% polyvinyl alcohol aqueous solution and pour it into the beaker. Add deionized water and make the volume to 4 g. Stir at room temperature for 2 hours at a speed of 600 r / min. Pour it into a PTFE mold and put it in a 60°C forced air drying oven until a film is formed. The sample is recorded as CP. The sample has strong plasticity and is in the shape of hard plastic. It is not the main matrix of the sample, so it is not necessary to test it.

[0083] Comparative Example 4

[0084] The only difference between this comparative example and Example 1 is that polyvinyl alcohol and polyvinyl butyral are not added. The specific steps are as follows:

[0085] Weigh 150 mg of corn straw core microparticles into a beaker, weigh 0.75 g of a 10 wt% gelatin aqueous solution, add deionized water and dilute to 4 g, stir at room temperature for 2 h, rotate at 600 r / min, pour into a PTFE mold, and place in a 60°C forced air drying oven until a film is formed. The sample is recorded as CB. This sample is very brittle, amber-like, and easily broken, so it is not necessary to test it.

[0086] Comparative Example 5

[0087] The only difference between this comparative example and Example 1 is that the bone glue is replaced by carrageenan, and polyvinyl alcohol and polyvinyl butyral are not added. The specific steps are as follows:

[0088] Weigh 150 mg of corn straw core particles and put them into a beaker. Weigh 0.75 g of a 10 wt% carrageenan aqueous solution, add deionized water and dilute to 4 g. Stir at room temperature for 2 h at a speed of 600 r / min. Pour the mixture into a PTFE mold and place it in a 60°C forced air drying oven until a film is formed. The sample is recorded as CA. This sample is soft and elastic with poor strength, so it is not necessary to test it.

[0089] Comparative Example 6

[0090] The only difference between this comparative example and Example 1 is that polyvinyl butyral is not added. The specific steps are as follows:

[0091] Weigh 150 mg of corn straw core microparticles and place them in a beaker. Weigh 1 g of a 7.5 wt% polyvinyl alcohol aqueous solution and pour it into the beaker. Continue to weigh 0.75 g of a 10 wt% bone glue aqueous solution, add deionized water and dilute to 4 g. Stir at room temperature for 2 h at a speed of 600 r / min, pour into a PTFE mold, and place in a 60°C forced air drying oven until a film is formed. The sample is recorded as CPBP-0h.

[0092] Test example

[0093] The samples prepared in Examples 1 to 4 and Comparative Example 6 were tested using a scanning electron microscope (SEM). Figures 1 and 2 As shown. Figure 1 It can be seen that the reverse side (bottom side) of the film substrate prepared with polyvinyl alcohol and gelatin presents a loose lamellar structure, while the front side (top side) presents a smooth and compact structure. This structure allows the front side of the composite film to remain stable in a humid environment, while the reverse side of the composite film remains stable in a dry environment, providing a new idea for the application of composite films in environments with humidity differences between the two sides. Figure 2 The cross-sectional view shows that the surface of the film soaked in PVB alcohol solution is covered with a dense hydrophobic layer with a certain thickness; the straw core particles present a flaky and smooth structure after molding.

[0094] The film thicknesses of the samples prepared in Examples 1 to 4 and Comparative Example 6 are shown in Table 1.

[0095] Table 1 Thickness of corn straw core-based composite film

[0096] project Comparative Example 6 Example 1 Example 2 Example 3 Example 4 Thickness (mm) 0.165 0.198 0.261 0.262 0.267

[0097] The FT-IR infrared spectra of corn straw core (CSC), polyvinyl alcohol (PVA), bone glue (BG), polyvinyl butyral (PVB), samples prepared in Examples 1 to 4 and Comparative Example 6 are shown in FIG. Figure 3 As stated.

[0098] The hydrophobicity test was conducted on the samples prepared in Examples 1 to 4 and Comparative Example 6 using a water contact angle tester. The results are as follows: Figure 4 As shown in the figure, the reverse side (bottom side) of the membrane substrate prepared with polyvinyl alcohol and bone glue is hydrophilic, while the front side (top side) is hydrophobic. The samples prepared in Examples 1 to 4 both have certain hydrophobic characteristics on the front and back sides.

[0099] The water vapor permeability coefficient (Pwv) of the samples prepared in the embodiments of the present invention was tested using a moisture permeability cup (using the test method in "GB / T 1037-2021 Plastic Film and Sheet Water Vapor Permeability Determination Cup Weight Gain and Weight Loss Method"). The water vapor permeability coefficients of the samples prepared in Examples 1 to 4 of the present invention and Comparative Example 6 and those of polylactic acid (PLA), polybutylene terephthalate-adipate (PBAT), CNF / CSC-100 (CN115926486A), and CCP-VVE-2 (CN117050386A) are compared as shown in the figure. Figure 5 As shown in Table 2. As can be seen from the figure, the straw core-based composite film prepared in the embodiment of the present invention has a high barrier property to water vapor.

[0100] Table 2 Water vapor permeability coefficient

[0101]

[0102] The stability of the material in a water environment is characterized by water absorption, dissolution rate and moisture absorption rate. The water absorption rate of the sample prepared in the embodiment of the present invention is tested using the test method in "ASTM-D570 Water Absorption Test". The sample after water absorption is placed in an oven and completely dried to a constant weight. The ratio of the sample loss mass to the dry weight is recorded as the dissolution rate. The sample is placed in different humidity environments and the ratio of the sample increase mass to the dry weight after 24 hours is measured as the moisture absorption rate. The results are as follows: Figure 6 and as shown in Table 3.

[0103] Table 3 Moisture absorption rate

[0104] project Comparative Example 6 Example 1 Example 2 Example 3 Example 4 Moisture absorption rate -97 RT (%) 23.3 20.4 14.6 11.2 10.5 Moisture absorption rate -75 RT (%) 14.5 12.2 12.7 12.4 12.1 Moisture absorption rate -57 RT (%) 6.8 4.0 3.7 2.3 2.5 Moisture absorption rate -44 RT (%) 7.6 4.4 3.5 3.2 2.3

[0105] Figure 6 The results showed that the original film was not stable in water. After being immersed in PVB for more than 24 hours, the composite film reached its maximum stability in water, with the water absorption rate reduced to 176.6% and the dissolution rate reduced to 23.5%.

[0106] The tensile strength and elongation at break of the samples prepared in Examples 1 to 4 and Comparative Example 6 were tested using the test method in GB / T 1040.1-2018 Determination of tensile properties of plastics. The results are as follows: Figure 7 The sample prepared in Example 2 has the highest tensile strength, which can reach up to 8.7 MPa, and the elongation at break is 4.0%.

[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A straw core-based composite film, characterized in that: It comprises a membrane substrate composed of straw core particles and a hydrophobic layer coated on the surface of the membrane substrate; Wherein, polyvinyl alcohol and bone glue are filled between the straw core particles; The material of the hydrophobic layer includes polyvinyl butyral.

2. The straw core-based composite film according to claim 1, characterized in that: The particle size of the straw core particles is 200-400 meshes.

3. The straw core-based composite film according to claim 1 or 2, characterized in that: The straw core particles include one or more of corn straw core particles, sunflower straw core particles or sesame straw core particles.

4. The straw core-based composite film according to claim 1, characterized in that: The alcoholysis degree of the polyvinyl alcohol is 87% to 89%; and / or The average molecular weight of the polyvinyl butyral is 90,000 to 120,000.

5. The straw core-based composite film according to claim 1, characterized in that: The thickness of the film substrate is 150 μm to 180 μm; and / or The penetration thickness of the hydrophobic layer in the membrane substrate is 5 μm to 20 μm.

6. The straw core-based composite film according to claim 1, characterized in that: The mass ratio of the straw core particles, polyvinyl alcohol, gelatin and polyvinyl butyral is 2:(0.5-1):(0.5-1):(0.5-2).

7. A method for preparing a straw core-based composite film according to any one of claims 1 to 6, characterized in that: The steps include: S1, dissolving polyvinyl alcohol and bone glue in water respectively to obtain polyvinyl alcohol solution and bone glue solution; dissolving polyvinyl butyral in an alcohol solvent to obtain a polyvinyl butyral solution; S2, mixing the straw core particles, polyvinyl alcohol solution and gelatin solution uniformly, and casting the mixture into a film to obtain a film substrate; S3, adding the film substrate into a polyvinyl butyral solution, impregnating, and drying to obtain a straw core-based composite film.

8. The method for preparing the straw core-based composite film according to claim 7, characterized in that: The concentration of the polyvinyl alcohol solution is 5wt% to 10wt%; and / or The concentration of the bone glue solution is 5wt% to 10wt%; and / or The concentration of the polyvinyl butyral solution is 5wt% to 15wt%; and / or In S3, the immersion temperature is 20°C to 40°C, and the immersion time is 12h to 48h.

9. Use of the straw core-based composite membrane according to any one of claims 1 to 6 in the preparation of a water-blocking and breathable membrane.

10. The use according to claim 9, characterized in that The water-blocking and breathable film is a packaging film, a moisturizing film, a sealing film or an inner core layer of a mask.

Citation Information

Patent Citations

  • Straw core nanocellulose composite membrane and preparation method and application thereof

    CN115926486A

  • Straw core-based composite film as well as preparation method and application thereof

    CN117050386A